Pelatihan Pembuatan Design Digital Marketing bagi UMKM untuk Meningkatkan Wawasan dan Pendapatan Masyarakat Desa Cikarageman, Setu, Bekasi - Akmaludin Akmaludin; Cepi Cahyadi; Suhardoyo Suhardoyo (Universitas Mathla'ul Anwar Banten, 2021)
DIGITAL MARKETING DESIGN TRAINING FOR MSMES TO INCREASE INSIGHTS AND COMMUNITY INCOME IN CIKARAGEMAN VILLAGE, SETU DISTRICT, BEKASI, WEST JAVA. Cikaregaman village, Setu sub-district, Bekasi district, West Java Province, is a village that has quite a lot of MSMEs, especially those driven by youth and youth youth groups who are eager to increase their level of welfare, but cannot simultaneously increase their daily needs. Seeing the continuous conditions like this, we identified the problems that arise, including first, the people in Cikaregaman Village, Setu District don't know about the promotion of products that will be sold to the market, the second is that many people already have smartphones, but cannot make optimal use of them. , especially in terms of the promotional media for the products they sell. Thus we provide solutions in the form of computer training to introduce digital marketing design applications in the manufacture of pamphlets and banners, which will be used as a media for promotion of community products in Cikarageman village, Setu sub-district, especially for MSMEs among youth, Karang Taruna youth in Cikarageman village, Setu sub-district. To realize our work program as lecturers in realizing the Tri Dharma of Higher Education, namely providing computer training in the form of a digital marketing design application with the Canva application in making their product promotions in order to increase knowledge on the use of smartphones as a promotional tool and increase the income of MSMEs, especially in the youth, youth and youth circles Cikarageman, Setu sub-district, Bekasi, West Java.